Respuesta :
SOLUTION:
Let's convert the problem into an equation. To do this, since we need 1 / 3 of 1 / 2, we simply divide 1 / 2 by 1 / 3 as displayed below:
= ( 1 / 2 ) ÷ ( 1 / 3 )
Next we change the division symbol into a multiplication symbol and write the reciprocal of the fraction after the division symbol.
= ( 1 / 2 ) ÷ ( 1 / 3 )
= ( 1 / 2 ) × 3
Now we simply solve the equation by writing the product of the two numbers.
= ( 1 / 2 ) × 3
= 3 / 2
Please mark as brainliest if you found this helpful! :)
Thank you <3
Let's convert the problem into an equation. To do this, since we need 1 / 3 of 1 / 2, we simply divide 1 / 2 by 1 / 3 as displayed below:
= ( 1 / 2 ) ÷ ( 1 / 3 )
Next we change the division symbol into a multiplication symbol and write the reciprocal of the fraction after the division symbol.
= ( 1 / 2 ) ÷ ( 1 / 3 )
= ( 1 / 2 ) × 3
Now we simply solve the equation by writing the product of the two numbers.
= ( 1 / 2 ) × 3
= 3 / 2
Please mark as brainliest if you found this helpful! :)
Thank you <3